Unveiling the Geometry of Culture: An Ethnomathematical Exploration of Transformation Geometry in Cimahi Batik Motifs - Purniati, Tia; Suhaedi, Didi (FKIP Universitas Lampung, 2025)
Mathematics played an essential role in daily life. However, mathematics learning in schools was often less connected to students' real-life contexts, so many of them struggle to understand mathematical concepts. Relating mathematics to everyday life was necessary for students to understand its relevance and benefits. This research aimed to explore the cultural values and concepts of transformation geometry embedded in Cimahi batik motifs. The method used in this study was ethnographic, with the research conducted in Lembur Batik, Cimahi, West Java, Indonesia. The research framework in ethnomathematics adopted four key questions to inform the framework used to facilitate research, “Where should observations be made from?,